2018
DOI: 10.1590/s1980-220x2017028703392
|View full text |Cite
|
Sign up to set email alerts
|

Fragilidade física e velocidade da marcha em idosos da comunidade: uma revisão sistemática

Abstract: RESUMO Objetivo: Identificar os desfechos dos estudos sobre velocidade da marcha e seu emprego como marcador de fragilidade física em idosos da comunidade. Método: Revisão sistemática da literatura realizada nas bases de dados LILACS, SciELO, MEDLINE/ PubMed, ScienceDirect, Scopus e ProQuest. Os estudos foram avaliados pelo STROBE e adotaram-se as recomendações do PRISMA. Resultados: Obtiveram-se 6.303 estudos, e 49 deles atenderam aos critérios de inclusão. Do total de estudos, 91,8% descreveram a forma de me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
32
0
6

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(45 citation statements)
references
References 75 publications
(105 reference statements)
2
32
0
6
Order By: Relevance
“…The study finding that people who use a car for going out walk faster is also an indication that higher physical functioning affects walking speed. In addition, a systematic review suggested that walking speed has traditionally been measured in the laboratory on an artificial walkway [12]. In this study, we used smartphone application data to measure walking speed in daily life, and our findings were similar to previous studies in terms of risk factor analysis.…”
Section: Discussionsupporting
confidence: 77%
“…The study finding that people who use a car for going out walk faster is also an indication that higher physical functioning affects walking speed. In addition, a systematic review suggested that walking speed has traditionally been measured in the laboratory on an artificial walkway [12]. In this study, we used smartphone application data to measure walking speed in daily life, and our findings were similar to previous studies in terms of risk factor analysis.…”
Section: Discussionsupporting
confidence: 77%
“…We have chosen midstance since it is known to have a important purpose in giving stability to the human body [4]. For the daily functionality of the body, standing on one or both feet, stability [39] and mobility have a significant purpose.…”
Section: Discussionmentioning
confidence: 99%
“…Midstance has been chosen because this is the first part of the single-leg support period and stability is a major concern in osteoarthritis (OA) patients, as the base of support decreases significantly, and the center of gravity moves to its highest point through leg extension furthermore in the gait cycle. The most important function of the lower limb is stability, so it is our job to prevent falls [4,5].…”
mentioning
confidence: 99%
“…Besides, the definition of frailty revolves around the onset of accelerated weight loss with an associated decrease of the mass and strength in the skeletal muscle (27). Furthermore, in a systematic literature review it was found that, in a 30.6% of the selected studies, there was an association between gait speed and disability, frailty, sedentary lifestyle, falls, muscular weakness, diseases, body fat, cognitive impairment, mortality, stress, lower life satisfaction, lower quality of life, and poor performance in quantitative parameters of gait (28).…”
Section: Introduction Contextmentioning
confidence: 99%